How to study and other skills for success in college - Deese, James 1921-; Deese, Ellin K. (McGraw-Hill, 1993)
This volume reflects the changes brought about by the computer revolution. It recognizes that how to study efficiently does not come naturally, and offers common sense advice that takes into account all the variables of student life. The book aims to help students: make good use of their study time; get the most out of textbooks and lectures; learn strategies for taking exams; improve their ability to write papers and reports; use the library to their best advantage; study maths, science, and foreign languages.